“No One Thinks of Greenland:” US-Greenland Relations and Perceptions of Greenland in the US from the Early Modern Period to the 20th Century - Ingo Heidbrink (CBS Open Journals, 2022)
The history of US-Greenland relations and the perception of Greenland in the US is a near complete historical desideratum with only few works dealing with the subject at all and those publications covering mainly the few well-known historic events. Neither US nor Danish or Greenlandic historians have dealt with the perception of Greenland in the US from Early Modern to today in its entirety. The article provides an overview of the history of perception of Greenland in the US and the bilateral relations of these countries from Early Modern to today, but more important also asks the question why this subject has been largely ignored. The title of John Griesemer’s novel “No one thinks about Greenland” is used as a parable to describe these reasons and the attitude of the US and US foreign policy towards Greenland. Furthermore, it is analyzed, why the US tried purchasing Greenland several times and why certain groups in the US had an interest to keep the US-Greenland relations in the shadows. It is also described how not purchasing Greenland made perfect sense for the US and generated a political vacuum on the island, that provided some unique opportunities for the US military. Throughout history it remained true that nearly nobody in the US thought about Greenland, resulting in a unique history of bi-lateral relations.